Initial Reports of the Deep Sea Drilling Project 1986
DOI: 10.2973/dsdp.proc.96.143.1986
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Data on Dissolved Organic Carbon and Sugar in Interstitial Water from the Mississippi Fan and Orca and Pigmy Basins, Deep Sea Drilling Project Leg 96

Abstract: Preliminary data on dissolved organic carbon (DOC) and dissolved sugars in interstitial water samples collected at Sites 618, 619, and 623 of Deep Sea Drilling Project Leg 96 are presented.At Site 618 in Orca Basin, the DOC content of the interstitial water peaks in the hypersaline sulfate reduction zone. The sugar content reaches a maximum and the DOC content begins to decrease at the depth of methane gas generation. Below that depth, the sugar and DOC contents are about constant.At Site 619 in Pigmy Basin, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
(8 reference statements)
1
6
0
Order By: Relevance
“…Previous studies of coastal (Starikova, 1970;Nissenbaum et al, 1971;Krom and Sholkovitz, 1977) and hemipelagic sedi ments (Michaelis et al, 1982;Ishizuka et al, 1986b) have dem onstrated that the bulk of dissolved organic carbon in marine pore waters is made up of complex HMW compounds. Nissen- (1971) and Krom and Sholkovitz (1977) argued that the HMW compounds are formed by condensation of LMW compounds released during biological degradation of sedimen tary organic carbon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies of coastal (Starikova, 1970;Nissenbaum et al, 1971;Krom and Sholkovitz, 1977) and hemipelagic sedi ments (Michaelis et al, 1982;Ishizuka et al, 1986b) have dem onstrated that the bulk of dissolved organic carbon in marine pore waters is made up of complex HMW compounds. Nissen- (1971) and Krom and Sholkovitz (1977) argued that the HMW compounds are formed by condensation of LMW compounds released during biological degradation of sedimen tary organic carbon.…”
Section: Discussionmentioning
confidence: 99%
“…They found that free carbohydrates and amino acids constituted less than 20% of DOC and that the relative proportion of these compounds de creased with depth in the core. At ODP Sites 618, 619, and 623, Ishizuka et al (1986b) reported concentrations of DOC between 23 and 225 mg C/L. They observed roughly parallel concentra tion profiles of sugars and DOC.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…No systematic depth trends were observed in this cases. Ishizuka et al (1986b) reported DOC concentrations between 23 and 225 mgC L -1 at ODP Sites 618, 619 and 623 on the Mississippi Fan and Orcha and Pigmy Basins. On the other hand, DOC concentrations at Sites 689 and 690 were one to two orders of magnitude lower than those at above sites (1.82-6.91 mgC L -1 ).…”
Section: Relationship Between Doc and Total Dissolved Amino Acids In mentioning
confidence: 99%
“…Since DFAA was a major fraction of THAA, low molecular weight (LMW, molecular weight less than 1000) fractions were small contributor for the DOC. Previous studies of coastal (Krom and Sholkovitz, 1977) and hemipelagic sediments (Michaelis et al, 1982;Ishizuka et al, 1986b) have demonstrated that the bulk of DOC in marine interstitial waters is made up of complex high molecular weight (HMW, molecular weight greater than 1000) fractions. Krom and Sholkovitz (1977) argued that the HMW compounds are formed by condensation of LMW compounds released during biological degradation of sedimentary organic carbon.…”
Section: Relationship Between Doc and Total Dissolved Amino Acids In mentioning
confidence: 99%